Prevalence and patterns of multimorbidity among the elderly in Burkina Faso: cross‐sectional study. Issue 11 (28th August 2014) - Hien, Hervé; Berthé, Abdramane; Drabo, Maxime Koiné; Meda, Nicolas; Konaté, Blahima; Tou, Fatoumata; Badini‐Kinda, Fatoumata; Macq, Jean
Abstract Objectives To assess the prevalence and distribution patterns of multimorbidity among urban older adults in Burkina Faso. Methods Cross‐sectional study among community‐dwelling elderly people aged ≥60 in Bobo‐Dioulasso. We performed interviews, clinical examination and medical record review. Multimorbidity was defined as co‐occurrence of at least two chronic diseases in one person whether as a coincidence or not. Results The overall prevalence of multimorbidity among older adults was 65%. Age ≥70 was associated with multimorbidity in multivariate analysis: adjusted OR = 1.65, 95% CI (1.01–2.68, P = 0.04). The most common chronic diseases were hypertension (82%) 95% CI (78; 86), malnutrition (39%) 95% CI (34; 44), visual impairments (28%) 95% CI (24; 33) and diabetes mellitus (27%) 95% CI (22; 31). Those aged ≥70 had significantly more malnutrition (50% vs. 31%, P = 0.0003) and osteoarthritis (8% vs. 3%, P = 0.01) than those aged 60–69. Conclusions The high prevalence of multimorbidity requires a reorganization of healthcare systems in sub‐Saharan Africa, especially in Burkina Faso. Interventions and care guidelines usually focused on individual diseases should be improved to better reflect this reality.